The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/app9061233
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Swelling Behavior of Expansive Soil at Different Depths under Unidirectional Seepage

Abstract: The swelling properties of expansive soil at different depths were investigated by the laboratory model test. It was experimentally found that the swelling deformation of different expansive soil layers was obviously different under unidirectional seepage. Pore solution collection boxes were designed to collect the pore solution of different soil layer interfaces during the saturation process. Cation concentration tests were then used to analyze the migration regulation of cations in these soil layers. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…3 , 4 , and 5 , the maximum S a of 18% and S p of 93 kPa is measured at MMC of 43%, (Ca/Na) T of 10–14, and (Ca/Na) L of 2–7. The results obtained in the present study are in well agreement with the studies reported by Shi et al 24 , She et al 72 , and Abd-Allah et al 73 , who have reported properties of MMC, chemical and swelling parameters that are found to be falling in the range of data produced by the presented study.…”
Section: Resultssupporting
confidence: 93%
“…3 , 4 , and 5 , the maximum S a of 18% and S p of 93 kPa is measured at MMC of 43%, (Ca/Na) T of 10–14, and (Ca/Na) L of 2–7. The results obtained in the present study are in well agreement with the studies reported by Shi et al 24 , She et al 72 , and Abd-Allah et al 73 , who have reported properties of MMC, chemical and swelling parameters that are found to be falling in the range of data produced by the presented study.…”
Section: Resultssupporting
confidence: 93%
“…Usually, the soil will shrink with the reduction of moisture content and swell with the increase in moisture content [ 8 , 9 ]. Clay soil has high plasticity, low support, and high shrinkage when the soil contains water [ 9 , 10 ]. This condition encouraged civil engineers to seek solutions in order to strengthen the soil through soil stabilization [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clay soil has high plasticity, low support, and high shrinkage when the soil contains water [ 9 , 10 ]. This condition encouraged civil engineers to seek solutions in order to strengthen the soil through soil stabilization [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Soil stabilization aims to increase the mechanical properties of the soil and also to control plasticity and shrinkage in soils containing excess water [ 4 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations